YIELD AND QUALITY OF POMEGRANATE AS INFLUENCED BY ORGANIC AND INORGANIC NUTRIENTS. - S. K. DUTTA RAY; P. V. TAKAWALE; R. CHATTERJEE; V. HNAMTE (The Bioscan, 2014)
Pomegranate is rich in sugar, vitamin, and minerals. Pomegranate is used not only as dessert fruit but it is also used as spice. An investigation was therefore undertaken to increase the production and quality of pomegranate with suitable nutrient management. Four levels of nitrogen (1000g, 400g, 300g and 200g plant -1) in the form of urea and neem cake (1kg plant -1) and in combinations, along with a common dose of 100g phosphorus (Single super phosphate) and 100g potassium (Muriate of potash) were applied. The fruits of the plants treated with 300g nitrogen + 1kg neem cake plant -1 recorded highest total soluble solids (12.29ºBrix), total sugar (10.74 %), reducing sugar (9.78%), non reducing sugar (1.09%) and ascorbic acid (21.93 mg 100 -1 mL of juice). The acidity was also recorded lower (0.39%) with this treatment.